A study of nerve conduction velocity in diabetic patients and its relationship with tendon reflexes (T-Reflex) - Haji Naghi Tehrani, Khadijeh (Acta Biomedica Atenei Parmensis, 2020)
Background and Objective: Neuropathy is one of the most common complications of diabetes mellitus. Neuropathy can cause sensory deficit, neurological disorder, organ ulcers, osteomyelitis, and amputation. Therefore, neurological examinations, determining the nerve conduction velocity and performing sensory and motor tests are important for timely diagnosis and treatment. The present study aimed to investigate the nerve conduction velocity in diabetic patients and its relationship with tendon reflexes. Materials and Methods: The present study was observational-cross sectional research carried out on 77 diabetic patients who admitted to the EMG / NCV Department of Shariati Hospital in the academic year 1996-1997. In all patients, the medical history of the patient (age, duration of diabetes, gender and age of onset of diabetes), neurological examination, nerve conduction velocity, heat test, vibration test, tendon reflexes, D.L and Amplitude were examined and recorded. Finally, the raw data obtained was entered into the IBM SPSS Statistics software and the important relationships between these variables were analyzed. Moreover, in present study, the statistical significance level (P-value) was considered less than 0.05. Results: The present study was conducted on a population consisting of 48 women and 29 men with diabetes. The age range of participants was 14-70 years old with an average age of 50.506 ± 7.50. The results of present study showed that the participants with clinical neuropathy (11.2 ± 7.2) had significantly longer duration of diabetes than the normal group and those participants with sub-clinical neuropathy (P-value = 0.12). Statistical analyses indicated that increase in age, increase in the duration of diabetes and the gender of male significantly made the nerve conduction velocity abnormal. The analysis of the response to neural reflexes indicated that the ratio of neurological disorders in the five nerves of the ankle and knee was generally higher in the abnormal group (the patients with nerve conduction disorder) compared to the normal (the patients with normal nerve conduction) and in some cases, such as the ulnar motor nerve of ankle (P-value = 0.010), and the ulnar motor nerve of knee motor -(P-value = 0.002) and also in the peroneal motor nerve of knee (P-value = 0.003) and the sural sensory nerve of knee -(P-value = 0.003), increase in neurological disorders was significant. Conclusion: Increase in age, increase in the duration of diabetes and the gender of male can significantly make the nerve conduction velocity abnormal.